2019
DOI: 10.1021/acs.jpcc.9b07874
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Hybridization Orbitals at the Charged Interface Initiates New Surface Reactions: A Quantum Mechanics Exploration

Abstract: Although the first report of Hofmeister effects is more than 130 years old, the origins of the Hofmeister series remain debated. In this study, quantum mechanics (QM) analyses, dispersion-corrected p-DFT calculations, and dynamic light scattering (DLS) determinations are combined with the aim to unravel such a scientific basis. QM analyses show that asymmetric hybridization occurs for the outer-shell nsnp z orbitals at charged interfaces, and the asymmetric sp z hybridization further initiates two unique pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 43 publications
(88 reference statements)
0
21
0
Order By: Relevance
“…However, according to theory of asymmetric hybridisation of outer shell orbitals of atom/cation in the external electric field arising from clay surface charges (Q. Li et al, 2019), the O atoms as well as the adsorbed cations at surface could be non‐classically polarised. It has been shown that cations like Na + and Mg 2+ with 2s2p outer orbitals have the weakest polarisation effects, and the interactions between these cations with surface O on clay were mainly composed of electrostatic interaction and non‐classical polarisation effects (Q. Li et al, 2019). On the other hand, the polarisation of K + , Ca 2+ with 3s3p (or other cations with outer shell number of n > 3) orbitals was significantly higher than that of n = 2 (e.g., Na + and Mg 2+ ), which provided the basis for the ‘polarisation‐induced covalent bonds’ between K + , Ca 2+ , Cs + and surface O on clay (Q. Li et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, according to theory of asymmetric hybridisation of outer shell orbitals of atom/cation in the external electric field arising from clay surface charges (Q. Li et al, 2019), the O atoms as well as the adsorbed cations at surface could be non‐classically polarised. It has been shown that cations like Na + and Mg 2+ with 2s2p outer orbitals have the weakest polarisation effects, and the interactions between these cations with surface O on clay were mainly composed of electrostatic interaction and non‐classical polarisation effects (Q. Li et al, 2019). On the other hand, the polarisation of K + , Ca 2+ with 3s3p (or other cations with outer shell number of n > 3) orbitals was significantly higher than that of n = 2 (e.g., Na + and Mg 2+ ), which provided the basis for the ‘polarisation‐induced covalent bonds’ between K + , Ca 2+ , Cs + and surface O on clay (Q. Li et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that cations like Na + and Mg 2+ with 2s2p outer orbitals have the weakest polarisation effects, and the interactions between these cations with surface O on clay were mainly composed of electrostatic interaction and non‐classical polarisation effects (Q. Li et al, 2019). On the other hand, the polarisation of K + , Ca 2+ with 3s3p (or other cations with outer shell number of n > 3) orbitals was significantly higher than that of n = 2 (e.g., Na + and Mg 2+ ), which provided the basis for the ‘polarisation‐induced covalent bonds’ between K + , Ca 2+ , Cs + and surface O on clay (Q. Li et al, 2019). That is, the interaction potential between K + , Ca 2+ , Cs + and surface O on clay was composed of the electrostatic potential, the non‐classical polarisation effect and the ‘polarisation‐induced covalent’ interaction energy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…26,27 Further studies have conclusively shown that the aforementioned ionic interface behavior can be enhanced with increases in ionic size. 28 Thereby, the newly discovered interaction forces probably play an essential role in the incomplete ion-exchange state of cation adsorption, and dominate the possible specic ion effects. However, such important issues have scarcely been involved in the current research.…”
Section: Introductionmentioning
confidence: 99%